Relation between blood pressure and genito-urinary symptoms in the years across the menopausal age. (4th July 2022) - Cagnacci, A.; Gambera, A.; Bonaccorsi, G.; Xholli, A.; ,
Abstract: Objectives: This study aimed to evaluate the relation between blood pressure (BP) or heart rate and genito-urinary symptoms in 504 women across the menopausal age (40–55 years old). Methods: In this multicenter, cross-sectional study, data of office systolic blood pressure (SBP), diastolic blood pressure (DBP) and heart rate were related to the presence of vaginal dryness, dyspareunia, vaginal atrophy (VA), recurrent urinary infection (RUI), hot flushes (HF) or menopausal status. Results: Vaginal dryness (coefficient of linear regression β  = 5.45, 95% confidence interval [CI] 2.01–8.89; p  = 0.0001), VA ( β  = 3.79, 95% CI 0.84–6.74; p  = 0.002) and RUI ( β  = 3.91, 95% CI 0.72–7.09; p  = 0.0163) were independently related to SBP. Vaginal dryness ( β  = 3.28, 95% CI 0.95–5.61; p  = 0.0058), and HF ( β  = 2.29, 95% CI 0.29–4.28; p  = 0.025) were independently related to DBP. Dyspareunia ( β  = 2.11, 95% CI 0.50–3.72; p  = 0.010) was independently related to heart rate. Hypertension was present in 17% of women. When corrected for body mass index (BMI), risk factors for hypertension were VA (OR 2.50, 95% CI 1.43–4.40; p  = 0.0014), RUI (OR 1.94 95% CI 1.06–3.52; p  = 0.0302) and HF (OR 2.01, 95% CI 1.15–3.50; p  = 0.0141). Conclusions: In women across the menopausal age, genito-urinary symptoms, more than HF, are associated with higher values of SBP, DBP, heart rate and hypertension.